Use of injections in healthcare settings worldwide, 2000: literature review and regional estimates - Hutin, Yvan J F (BMJ Publishing Group Ltd., 2003)
Objective To describe injection practices worldwide in terms of frequency and safety. Design Literature review. The global burden of disease project of the World Health Organization defined 14 regions on the basis of geography and mortality patterns. Data sources included published studies and unpublished WHO reports. Studies were reviewed by using a standardised decision making algorithm to generate region specific estimates. Setting Healthcare facilities, both formal and informal. Data sources: General population and users of healthcare facilities. Main outcome measure Annual number of injections per person and proportion of injections administered with syringes or needles, or both, reused in the absence of sterilisation. Results The analysis excluded four regions (predominantly affluent, developed nations) where reuse of injection equipment in the absence of sterilisation was assumed to be negligible. In the 10 other regions, the annual ratio of injections per person ranged from 1.7 to 11.3. Of these, the proportion administered with equipment reused in the absence of sterilisation ranged from 1.2% to 75.0%. Reuse was highest in the South East Asia region “D” (seven countries, mostly located in South Asia), the eastern Mediterranean region “D” (nine countries, mostly located in the Middle East crescent), and the western Pacific region “B” (22 countries). No information regarding injection safety was available for Latin America. Conclusions Overuse of injections and unsafe practices are still common in developing and transitional countries. An urgent need exists to use injections safely and appropriately, to prevent healthcare associated infections with HIV and other bloodborne pathogens.